Developing Standards for Assessing Circulatory and Respiratory Function of First-Year Male Students Majoring in Athletics, Swimming and Volleyball at Hanoi University of Physical Education and Sports - Tuong, Tran Dinh (International Journal of Humanities and Education Development (IJHED), 2022)
By routine research methods in physical training and sports, the article tested the representativeness of the mean and the normal distribution of the circulatory and respiratory indices of the first-year male students at the university. Hanoi University of Physical Education and Training, from which to develop classification standards, grading scale, and general evaluation criteria for circulatory and respiratory functions of male first-year male students of Hanoi University of Sports and Education.